Improving Vocational High School Quality: Link and Match, Teacher Professional Competence, and School Culture - Tommy Candra Hermawan; Ghufron Abdullah; Aryo Andri Nugroho; Muhammad Hilal Sudarbi (Yayasan Keluarga Guru Mandiri, 2026)
This study addresses the persistently low absorption of vocational high school graduates in Kendal Regency, Indonesia, despite the region's strategic position within a special economic zone that demands a skilled workforce. The study aims to examine the influence of the link and match program, teachers' professional competence, and vocational school culture on improving the quality of vocational education and its relevance to graduate employability. A quantitative correlational research design was employed, involving 219 vocational teachers selected through proportional random sampling. Data were collected using validated questionnaires and analyzed using multiple regression and correlation techniques. The results reveal that the link and match program significantly contributes to vocational education quality improvement (54.2%), followed by teachers' professional competence (24.4%) and school culture (24.1%). Collectively, these variables explain 76.7% of the variance in vocational education quality. The findings indicate that effective industry–school alignment, continuous professional development of teachers, and the internalization of industrial work culture are critical factors in enhancing graduate readiness and employability. This study contributes to the field of vocational education by providing empirical evidence on an integrated model of quality improvement that supports stronger alignment between vocational schools and labor market demands.